Choreoathetosis with Gabapentin - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
A 37-year-old man with severe mental retardation since birth and intractable epilepsy treated with AED polytherapy developed choreoathetosis and orofacial dyskinesia within 5 days of introducing gabapentin (GBP) at the Department of Neurology, West Virginia University, Morgantown, WV.